Triple Negative Breast Cancer: A Review - Mercado, Cecilia; Cangiarella, Joan; Guth, Amber A. (Current Women's Health Reviews, 2009)
Triple negative breast cancer has recently been recognized as a distinct subtype of breast cancer. While TNBC and basal-type breast cancers are not identical, the terms are often used synonomously. TNBC have a poorer prognosis than other molecular subtypes of breast cancer. There are no known targeted agents, leaving chemotherapy as the primary adjuvant therapy. TNBC are associated with BRCA1 mutations, are more common in African-American women, and have a more aggressive clinical course, with high early rates of metastatic disease and early relapse. Current research is examining epidemiologic features associated with TNBC, and searching for effective targeted therapy.
Keywords: racial/ethnic differences in breast cancer